THE INSURANCE IN THE FORMATION OF AN INVESTMENT ENVIRONMENT (International Journal of Innovative Technologies in Economy, 2018)
The article discusses the role of insurance in the formation of an investment environment. It is known that no country in the world has been able to secure economic growth without developing investment activity, this is also the case in the Republic of Armenia. The share of foreign direct investment in GDP in different countries varies from 100 to 11-13 %. In Armenia the highest level was in 2011-66,3 %, in 2016 it complied 5,4 % (GDP-10572,3 million US dollars, foreign direct investments – 567,99 million US dollars). The aim of the study is to justify the importance of insurance of investment risks for attracting foreign investments in Armenia.